Profile of cases of tetanus diagnosticated during 10 years in a reference hospital in the state of Alagoas, Northeastern Brazil (Research, Society and Development, 2022)
Objective: This research aimed to evaluate the clinical-epidemiological profile of cases of accidental tetanus, registered in a Reference Hospital for the treatment of infectious diseases, in the State of Alagoas, northeast region of Brazil, from January 2007 to December 2017. Methodology: The information was obtained through the database of the referred institution and that were registered in the Sistema de Informação de Agravos de Notificação. Data were tabulated in Microsoft Office Excel 2016 and statistically analyzed in Statistical Products and Service Solutions for Windows 12. Results: In the researched period, 67 cases of tetanus were diagnosed. The statistically significant social and epidemiological variables were: male sex (91%), urban area of residence (83.10%) and non-vaccination status of the infected (69%). Also noteworthy is the location of the injury in the region of the lower limbs (66.6%), cases caused by perforating wounds (36.7%), healing (53.1%) and the predominant age group from 18 to 49 years (67.2%). Trismus was the most evident clinical manifestation, being present in all cases. Of those evaluated, 45.3% died due to the disease. Conclusions: It is understood that the situation of accidental tetanus in Alagoas is suggestive of a deficit in the scope of primary prevention (vaccination), requiring greater work to disseminate and encourage immunoprevention among the population, especially among the age group from 18 to 49 years, which had a higher incidence in this study.